Morphology and connectivity of retinal horizontal cells in two avian species - Günther, Anja; Balaji, Vaishnavi; Leberecht, Bo; Forst, Julia J.; Rotov, Alexander Y.; Woldt, Tobias; Abdulazhanova, Dinora; Mouritsen, Henrik; Dedek, Karin (Frontiers in Cellular Neuroscience, 2025)
In the outer vertebrate retina, the visual signal is separated into intensity and wavelength information. In birds, seven types of photoreceptors (one rod, four single cones, and two members of the double cone) mediate signals to >20 types of second-order neurons, the bipolar cells and horizontal cells. Horizontal cells contribute to color and contrast processing by providing feedback signals to photoreceptors and feedforward signals to bipolar cells. In fish, reptiles, and amphibians they either encode intensity or show color-opponent responses. Yet, for the bird retina, the number of horizontal cell types is not fully resolved and even more importantly, the synapses between photoreceptors and horizontal cells have never been quantified for any bird species. With a combination of light microscopy and serial EM reconstructions, we found four different types of horizontal cells in two distantly related species, the domestic chicken and the European robin. In agreement with some earlier studies, we confirmed two highly abundant cell types (H1, H2) and two rare cell types (H3, H4), of which H1 is an axon-bearing cell, whereas H2-H4 are axonless. H1 cells made chemical synapses with one type of bipolar cell and an interplexiform amacrine cell at their soma. Dendritic contacts of H1-H4 cells to photoreceptors were type-specific and similar to the turtle retina, which confirms the high degree of evolutionary conservation in the vertebrate outer retina. Our data further suggests that H1 and potentially H2 cells may encode intensity, whereas H3 and H4 may represent color opponent horizontal cells which may contribute to the birds’ superb color and/or high acuity vision.